2006
DOI: 10.1002/jbm.a.30713
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of OI type III bone tissue measured by nanoindentation

Abstract: Nanoindentation was used to characterize the intrinsic mechanical properties of bone tissue from eight (8) children with type III Osteogenesis Imperfecta (OI). The bone samples were harvested from the cortex portion at the site of bowing (the mid 2/3 of the shaft of the tibia/femur). Unlike normal bone tissue, OI type III cortical bone exhibited more isotropic material properties. Young's modulus and hardness values measured in the longitudinal direction did not show significant differences from the transverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
2
29
0
1
Order By: Relevance
“…Furthermore, specimens in the current study were fresh-frozen and untreated, whereas those in the nanoindentation studies were dehydrated, a process that has been shown to increase modulus results [6365]. Unlike previous data from a nanoindentation study, which suggested that OI bone may exhibit more isotropic properties than normal tissue [32], results from the current study demonstrated clear anisotropy in bone material properties at the mesoscale within this population, with the transverse properties being approximately equal to one third of their longitudinal counterparts. These observations indicate that the preferential orientation of the vascular porosity network is likely to play an important role in the anisotropic behavior of OI bone at the mesoscale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, specimens in the current study were fresh-frozen and untreated, whereas those in the nanoindentation studies were dehydrated, a process that has been shown to increase modulus results [6365]. Unlike previous data from a nanoindentation study, which suggested that OI bone may exhibit more isotropic properties than normal tissue [32], results from the current study demonstrated clear anisotropy in bone material properties at the mesoscale within this population, with the transverse properties being approximately equal to one third of their longitudinal counterparts. These observations indicate that the preferential orientation of the vascular porosity network is likely to play an important role in the anisotropic behavior of OI bone at the mesoscale.…”
Section: Discussionmentioning
confidence: 99%
“…Within that microstructural scale, the elastic modulus of bone tissue was found to be higher in children with severe or moderately severe OI (types III and IV) vs. age-matched controls [25], and this property was slightly higher in children with mild (type I) vs. severe (type III) OI [31]. Interestingly, contrary to observations in normal bone tissue [3537], no significant difference in modulus was observed between indents taken parallel vs. perpendicular to the long bone axis [32], which led to the speculation that OI bone may exhibit more isotropic properties than does typical bone. These results confirm that bone material properties are affected in OI, however, important limitations with these studies should be acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of the anabolic effect of Sr, the slight decrease in bone hardness may result from the enhanced formation of a less mineralized new bone. E / H is useful in the evaluation of the overall deformation characteristics during indentation and is proportional to the fracture toughness of the bone [35]. Higher E / H values correspond to a more ductile material, while lower E / H values generally indicate a more brittle material.…”
Section: Discussionmentioning
confidence: 99%
“…Although modern biomechanical assessments such as nanoindentation or scanning acoustic microscopy may provide microscopic mapping of the mechanical properties of bone,29, 30 the properties at the implant interface still cannot be directly measured. Thus, in this study we generated functional apparent moduli (FAMs) by simulating the implant loading situation and extrapolation via FE modeling to match the microscopic data.…”
Section: Discussionmentioning
confidence: 99%